Functional divergence of FimX in PilZ binding and Type IV pilus regulation - Qi, Yaning (2013)
Type IV pili (T4P) are polar surface structures that play important roles in bacterial motility, biofilm formation, and pathogenicity. The protein FimX and its orthologs are known to mediate T4P formation in the human pathogen Pseudomonas aeruginosa and some other bacterial species. It was reported recently that FimXXAC2398 from Xanthomonas axonopodis pv. citri interacts with PilZXAC1133 directly through the nonenzymatic EAL domain of FimXXAC2398. Here we present experimental data to reveal that the strong interaction between FimXXAC2398 and PilZXAC1133 is not conserved in P. aeruginosa and likely other Pseudomonas species. In vitro and in vivo binding experiments showed that the interaction between FimX and PilZ in P. aeruginosa is below the measurable limit. Surface plasmon resonance assays further confirmed that the interaction between the P. aeruginosa proteins is at least more than 3 orders of magnitude weaker than that between the X. axonopodis pv. citri pair. The N-terminal lobe region of FimXXAC2398 was identified as the binding surface for PilZXAC1133 by amide hydrogen-deuterium exchange and site-directed mutagenesis studies. Lack of several key residues in the N-terminal lobe region of the EAL domain of FimX is likely to account for the greatly reduced binding affinity between FimX and PilZ in P. aeruginosa. All together, the results suggest that the interaction between PilZ and FimX in Xanthomonas species is not conserved in P. aeruginosa due to the evolutionary divergence among the FimX orthologs. The precise roles of FimX and PilZ in bacterial motility and T4P biogenesis are likely to vary among bacterial species.